(untitled) (World Bulletin of Public Health, 2024)
Onco Med-Chemistry focuses on designing and developing cancer therapies by integrating chemistry, biology, and pharmacology. It targets processes similarly carcinogenesis, tumor advancement, and drug resistance to create agents such as kinase inhibitors, immune checkpoint modulators, and antibody-drug conjugates. Tools like structure-based design and highthroughput screening are vital for innovation in this field.